PROBLEMS OF ENSURING SECURITY IN THE INFORMATION FIELD IN THE CONDITIONS OF TODAY'S GLOBALIZATION - Sayfiddin Imomovich Ibragimov (Western European Studies, 2025)
The article is devoted to the information culture formation level of the present period of transition to the information society; targeted use of modern technologies in the processing of orders and distribution of computer equipment
Keywords: information attack; globalization; process of globalization